Smoking cessation, weight gain, and DRD4 -521 genotype - Munafò, MR; Murphy, M; Johnstone, E (2006)
We investigated change in body mass index following long-term smoking cessation in a representative cohort of treatment-seeking heavy smokers in the United Kingdom, to determine the extent of long-term weight gain in successful quitters versus continuing smokers. We further investigated whether DRD4 genotype moderated any weight gain in either group. Smoking cessation was associated with an increase in BMI, and persisted up to 8 years after smoking cessation. Ex-smokers at 8-year follow-up weighed over 2.5 kg/m3 more on average than they did at baseline, while participants who were smokers at both baseline and 8-year follow-up did not demonstrate any change in BMI. We did not observe an interaction between smoking status and DRD4 genotype. However, independently of the weight gain among those who stopped smoking during the course of the study, DRD4 genotype was significantly associated with BMI, with possession of the -521 C-allele associated with increased BMI. The magnitude of increase in BMI following smoking cessation, and the persistence of this change at 8-year follow-up, suggests that health benefits associated with smoking cessation may to some extent be negated by the detrimental effects on health of associated weight gain. Smoking cessation programmes should therefore consider incorporating follow-up support to promote weight loss among those who successfully stop smoking. © 2006 Wiley-Liss, Inc.